Practice as research in animation: A provisional engagement. Issue 1 (1st August 2020) - Nelson, Robin
Let me start with a confession. Though for years, I have had an interest in animation and have observed students engaged in puppet, paper and plasticine processes of animation by analogue and digital means, I have myself never constructed an animated sequence. Why, then, have I been invited to write a contribution to this collection? For philosophical and political reasons related to a lifelong engagement with arts and screen media practices and education, I have developed expertise in what some call artistic research and I prefer to call practice as research (PaR). In particular, I have developed an epistemological model for PaR, which sets three modes of knowing ‐ know-how, know-what and know-that ‐ in dynamic inter-relation. In what follows, I place my specialist terms in italics to mark them out.